### Present Remotely

Send the link below via email or IM

• Invited audience members will follow you as you navigate and present
• People invited to a presentation do not need a Prezi account
• This link expires 10 minutes after you close the presentation

Do you really want to delete this prezi?

Neither you, nor the coeditors you shared it with will be able to recover it again.

# Fatin, Favad, and Daniyal Present:

No description
by

## Fatin Nawaz

on 1 April 2015

Report abuse

#### Transcript of Fatin, Favad, and Daniyal Present:

Boolean Algebra and Logic
Q.7 Identify the law of Boolean algebra upon which each of the following equalities is bound

(a) A¬B + CD + A¬CD + B = B + A¬B +A¬CD + CD

(b) AB¬CD + ¬(ABC) = D¬CBA + ¬(CBA)

(c) AB(CD+E¬F+GH) = ABCD + ABE¬F + ABGH

Ans.

(b) Commutative law of multiplication

(c) Distributive law
Q1. Using Boolean notation, write an expression that is 1 whenever one or more of its variables (A, B, C, and D) are 1s.

Ans. X = A + B + C + D

Q.9 Apply DeMorgan's theorems to each expression:
(a) ¬(A+¬B) (b) ¬(¬AB) (c) ¬(A+B+C) (d) ¬(ABC)
(e) ¬(A(B+C)) (f) ¬(AB) + ¬(CD)
(g) ¬(AB + CD) (h) ¬((A+¬B)(¬C+D))

(a) ¬(A+¬B) = ¬A¬(¬B) = ¬AB
(b) ¬(¬AB) = ¬(¬A) + ¬B = A + ¬B
(c) ¬(A+B+C) = ¬A¬B¬C
(d) ¬(ABC) = ¬A + ¬B + ¬C
(e) ¬(A(B+C)) = ¬A + ¬(B+C) = ¬A + ¬B¬C
(f) ¬(AB) + ¬(CD) = ¬A + ¬B + ¬C + ¬D
(g) ¬(AB + CD) = ¬(AB)¬(CD) = (¬A+¬B)(¬C+¬D)
(h) ¬((A+¬B)(¬C+D)) = ¬(A+¬B) + ¬(¬C+D) = ¬AB + C¬D
Q. 12 Write the Boolean Expression for each of the following logic gates
(a) (b) (c) (d)

Ans.

(a) AB = Q

(b) A + B = Y

(c) ¬A = Q

(d) A + B + C = Output
Q.19 Using Boolean algebra techniques simplify the following expressions as much as possible:

(a) A(A+B) (b) A(¬A + AB) (c) BC + ¬BC (d) A(A + ¬AB) (e) A¬BC + ¬ABC + ¬A¬BC

Ans.

(a) A(A+B) = AA + AB = A + AB = A(1 + B) = A

(b) A(¬A + AB) = A¬A + AAB = 0 + AB = AB

(c) BC + ¬BC = C (B + ¬B) = C(1) = C

(d) A(A + ¬AB) = AA + A¬AB = A +(0)B = A

(e) A¬BC + ¬ABC + ¬A¬BC = A¬BC + ¬AC(B + ¬B) = A¬BC + ¬AC = C(¬A + A¬B) = C(¬A + ¬B) = ¬AC + ¬BC

Q.23 Convert the following expressions to sum of products form:

(a) (A+B)(C+¬B) (b) (A + ¬BC)C (c) (A+C)(AB+AC)

Ans.

(a) (A+B)(C+¬B) = AC + BC + A¬B + B¬B = AC + A¬B + BC

(b) (A + ¬BC)C = AC + ¬BCC = AC + ¬BC

(c) (A+C)(AB+AC) = AAB + AAC + ABC + ACC = AB + AC + ABC + ACC = (AB + AC)(1 + C) = AB + AC
Q.31 Develop a truth table for each of the following standard SOP expressions.

(a) A¬BC + ¬AB¬C + ABC (b) ¬X¬Y¬Z + ¬X¬YZ + XY¬Z + X¬YZ + ¬XYZ
Full transcript